Keeping bees for better nutrition - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Beekeeping in Africa by Stephen Adjare 1990, 130pp ISBN 92 5 1027943 Publications Division, FAO Via delle Terme di Caracalla 00100 Rome, ITALY